Strengthening digital literacy and political culture for gen-Z through Pancasila education learning in higher education - Muhajir; Abdul Latief; Monica Tiara (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This article reviews the importance of political culture and digital literacy for Generation Z as a prospective demographic group. It examines how Pancasila education contributes to the development of Gen-Z's political culture and literacy in higher education. Using a mixed-method research approach with a sequential transformative strategy model, the study transforms one type of data into another after collecting and analyzing quantitative and qualitative data independently. Research findings indicate that trending topics, viral hashtags, FYP, news feeds, CC, and social media algorithms form the foundation of Gen-Z's digital political literacy and culture. This illustrates that, despite avoiding direct practice, Gen-Z exhibits a keen interest in digital politics. Consequently, Pancasila education provides Gen-Z members with opportunities to become competent political players and participants. The study also shows how Pancasila education incorporates digital-based political literacy and culture by emphasizing civic duties and integrating more "real" materials and ideals. The findings suggest that Pancasila education can enhance Gen-Z's digital political literacy and culture by making the curriculum more relevant to their daily lives and digital experiences. This approach not only strengthens digital literacy but also instills a deep understanding of ethical and responsible citizenship, aligning with the context of nationalism and Indonesian identity. The study concludes that integrating Pancasila values into digital political education is crucial for developing critical thinking skills and fostering civic awareness among Gen-Z, preparing them to navigate the complex digital landscape responsibly.